Comparison of ACL Strain in the MCL-Deficient and MCL-Reconstructed Knee During Simulated Landing in a Cadaveric Model. (April 2017) - Mancini, Eric J.; Kohen, Robert; Esquivel, Amanda O.; Cracchiolo, Allison M.; Lemos, Stephen Edward
Background: Noncontact anterior cruciate ligament (ACL) injury after valgus landing has been reported and studied biomechanically. However, the role of the medial collateral ligament (MCL) in dissipating these forces has not been fully elucidated. Purpose/Hypothesis: The purpose of this study was to investigate the role that the MCL plays in ACL strain during simulated landing. The hypothesis was that ACL strain would increase significantly in MCL-incompetent knees compared with the native knee and that reconstructing the MCL would return the values to those of the intact knee. Study Design: Controlled laboratory study. Methods: Eight fresh-frozen human cadaveric knees were used in this study. A materials testing machine applied a force of 2× body weight over 60 milliseconds to simulate landing after a jump. The knees were tested in 12 loading conditions, consisting of full extension or 15° of flexion combined with 7° of valgus or neutral alignment while the tibia was in external rotation, neutral rotation, or internal rotation. This test procedure was repeated on each specimen with the MCL transected and reconstructed. The superficial and deep MCL was transected along with the posterior oblique ligament, which was thought to simulate a worst case scenario. The MCL was reconstructed by use of semitendinosus and gracilis tendon grafts. Results: During internal rotation at 0° of flexion and 0° of valgus, both the intact ( P = .005) and the reconstructed ( P = .004) MCL states placed significantly lower strain on the ACL than did the transected MCL. The reconstructed MCL state at 0° of flexion and 7° of valgus ( P = .049) along with 15° of flexion and 0° of valgus ( P = .020) also placed significantly lower strain on the ACL than did the transected MCL. For external rotation testing at 0° of flexion and 7° of valgus, the reconstructed MCL state placed significantly lower strain on the ACL than did the transected MCL ( P = .039). Finally, during neutral rotation, the ACL strain at 0° of valgus and 0° of flexion, and at 7° of valgus and 0° of flexion was significantly lower for the MCL-intact groups ( P < .028) and MCL-reconstructed groups ( P < .016) than the MCL-transected groups. Conclusion: The current findings demonstrate that during valgus landing, a knee with an incompetent MCL puts the ACL under increased strain. These values are highest in full extension with the tibia in internal and neutral rotation. This increased strain can be reduced to baseline levels with reconstruction. Clinical Relevance: A knee with an incompetent MCL puts the ACL under increased strain. Once the MCL has healed in an elongated manner, MCL reconstruction should be considered.